The Influence of Colorism on the Hair Experiences of African American Female Adolescents - Lakindra Mitchell Dove (Genealogy, 2021)
This article addresses the prevalence of colorism among the hair care narratives of African American female adolescents. Eleven interviews were conducted to explore the connection between hair and sense of self and self-esteem. During data collection and analysis, the theme surrounding colorism emerged, as many participants discussed its influence on hair, recalling traumatic hair and colorist experiences. This article focuses on the analysis of these narratives using the colorist-historical trauma framework. Three themes emerged: (1) colorist experiences; (2) perceptions of good hair; and (3) the influence of White beauty standards. These themes reflect how participants conceptualized the implications of colorism and its impact on their psychosocial and emotional well-being. The article highlights how colorism is embedded in their lived experiences and how participants combated the presence of colorism perpetuated by family, peers, and society, to embrace their identities. The article outlines the implications of collective efforts to decolonize hair and promote healing and liberation through actions such as the natural hair movement, legal efforts to protect hairstyle preferences in schools and the workplace, and overall awareness of the perception of Black women in media. It also discusses shifts in attitudes, perspectives, and beliefs regarding hair among younger generations.